2019
DOI: 10.1002/jae.2706
|View full text |Cite
|
Sign up to set email alerts
|

The response of asset prices to monetary policy shocks: Stronger than thought

Abstract: Summary Standard macroeconomic theory predicts rapid responses of asset prices to monetary policy shocks. Small‐scale vector autoregressions (VARs), however, often find sluggish and insignificant impact effects. Using the same high‐frequency instrument to identify monetary policy shocks, we show that a large‐scale dynamic factor model finds overall stronger and quicker asset price reactions compared to a benchmark VAR, both on euro area and US data. Our results suggest that incorporating a sufficiently large i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 64 publications
(84 reference statements)
1
18
1
Order By: Relevance
“…Based on euro area data,Alessi and Kerssenfischer (2016) find similar results for asset prices more generally: Corporate bond yields, exchange rates, and stock and house prices all respond rapidly in the DFM framework, but only delayed and mildly in VARs.…”
mentioning
confidence: 62%
“…Based on euro area data,Alessi and Kerssenfischer (2016) find similar results for asset prices more generally: Corporate bond yields, exchange rates, and stock and house prices all respond rapidly in the DFM framework, but only delayed and mildly in VARs.…”
mentioning
confidence: 62%
“…A strand of recent literature emphasizes on the new transmission mechanism measures, and predicts that there will be rapid responses of the economy, particularly towards monetary policy shocks. Using the same high-frequency instruments to identify monetary policy shocks, in their analysis (Alessi & Kerssenfischer, 2019) revealed that large-scale dynamic factor models find overall stronger, as well as quicker asset price reactions, as compared to a benchmarked VAR model. They further suggested that incorporating a sufficiently large information set is crucial in estimating monetary policy effects.…”
Section: Literaturementioning
confidence: 99%
“…Simultaneously, there are almost no case studies on emerging countries' stock markets, in particular Ukraine. The return of the national stock markets is usually significant and negative to the positive "surprises" of the banking regulators' monetary decisions regarding the discount rate, and vice versa (e.g., Alessi & Kerssenfischer, 2019;Jarociński & Karadi, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%